Active break and work climate in academic and administrative areas of Universidad Peruana Unión, 2018 - Agata Samantha Ibañez Asto (2019)
Objective: To determine the relationship between the level of practice of Active Pause and LaborClimate in academic and administrative areas of the Universidad Peruana Unión. Methodology:The study design was non-probabilistic quantitative, descriptive type, cross-sectional correlation; Theactive pause survey and the work climate were applied to 200 people who previously participated inthe “Active Pause at Universidad Peruana Unión” program “Active Pause at the Universidad PeruanaUnión”. Results: The 59.5% sometimes practice the active pause and 86% maintain a good workingclimate, in the statistical analysis of correlation Tau-b of Kendall had a p-value score = 0.307, whichindicates that there is no relationship between active pause and work climate, as well as the dimensionsof Organization p-value = 0.178, Communication p-value = 0.525, Working conditions p-value = 0.376which also have no significant relationship, unlike the dimensions of Social interaction p-value = 0.038and that of Identity and belonging p-value = 0.025, which have a significant relationship with the activepause variable. Conclusion: It was not found a relationship in both variables, nor in three dimensions(organization, communication and working conditions), only in two of them (social interaction andidentity and belonging). statistically significant correlation between CVR and lifestyle (p=0.234),nevertheless it was found a correlation between CVR and eating habits (p=0.012).